Sequence based analysis of fungi associated with decomposition - Embrandiri, Asha; Mohamad, Ahmad Najib; Mohd Omar, Suhaila; Zainuddin, Nurul Syakira; Ahmad Roseli, Nur Syuhadah; Sharif, Mohd Faez; Abdul Hamid, Azzmer Azzar; Jamaludin, Mohd Hafiz; Mohamad, Mohd Azrul Naim (2018)
Phylogenetic analysis of the fungi species cultivated from fish waste compost provides crucial information to observe the evolutionary relatedness of fungi. This helps to provide an understanding of the process of composting and improving the quality of compost (nitrogen rich fertilizer). In this study, fungi species of fish waste compost containing ‘18s rRNA” were retrieved in FASTA format from the NCBI database formed the basis of this study. A sequence assembly program CAP3 for EST (Expression Sequence Tagging) to assemble the sequences into sets of contiguous sequences and single sequences was used. Thereafter 2 nearest neighbor sequences and percentage of similarity of the results of the above were retrieved using Basic Local Allignment Search Tool (BLAST) at >98% similarity index. The OTU sequences aligned via SINA (v1.2.11) Web Aligner and results imported into ARB software database. Consequently, via a series of applications: Gblocks and MrBayes the final format in .tre is obtained and imported back into existing ARB tree. The phylogenetic tree was thus constructed separately by exporting long, short and NN sequences using the ARB parsimony tool.